2020
DOI: 10.1080/11104929.2020.1731136
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impacts of vehicle wash wastewater on surface water quality through physico-chemical and benthic macroinvertebrates analyses

Abstract: Vehicle wash wastewater (VWW) contains a wide range of contaminants and discharge of such contaminated wastewater into the surface water bodies degrade water quality and affect aquatic ecosystems. This study, presents an impacts of discharging VWW into the stream Olarong Chhu in Thimphu and river Paa Chhu in Paro using water chemistry and benthic macroinvertebrates data sets obtained over a period of 6 months. Water samples and benthic macroinvertebrates were sampled once in a month from upstream, impact, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
(31 reference statements)
0
11
0
1
Order By: Relevance
“…Apesar da aparente preocupação e conhecimento das questões sanitárias do rio, algumas pessoas realizam lavagens de veículos às suas margens, e que, somado ao despejo de esgoto doméstico, potencializa o problema sanitário. Os resíduos oriundos da lavagem de veículos geralmente incluem fósforo, nitrogênio, surfactantes, matéria orgânica, metais pesados, resíduos de hidrocarbonetos derivados do petróleo, entre outros, que quando descartados na água do rio agravam o problema sanitário (Rai et al, 2020).…”
Section: Discussionunclassified
“…Apesar da aparente preocupação e conhecimento das questões sanitárias do rio, algumas pessoas realizam lavagens de veículos às suas margens, e que, somado ao despejo de esgoto doméstico, potencializa o problema sanitário. Os resíduos oriundos da lavagem de veículos geralmente incluem fósforo, nitrogênio, surfactantes, matéria orgânica, metais pesados, resíduos de hidrocarbonetos derivados do petróleo, entre outros, que quando descartados na água do rio agravam o problema sanitário (Rai et al, 2020).…”
Section: Discussionunclassified
“…With the country opening its border only a few decades ago, trade with neighboring countries has led to the opening of new factories, and construction of roads and other infrastructure has been increasing. Modernization has lead new industries to open such as mechanized car washes, swimming pools, and water parks [57,58]. Water is also used for sanitation purposes and to keep the surroundings clean.…”
Section: Water Use In Bhutanmentioning
confidence: 99%
“…A survey was performed to implement a water quality database for major water resources in Bhutan. The survey found that except for a few localized urban areas, water in Bhutan is safe on a large scale and Bhutan's waterways are exceptionally oxygenated, marginally basic with low conductivity, and have no hints of salinity [58]. As Bhutan focuses on enhancing water security and climate change adaptation, a National Adaption Plan was launched in 2019 with the United Nations Development Program (UNDP) and Green Climate Fund [71].…”
Section: Water Resource Developmentmentioning
confidence: 99%
“…Pb can come from lead paints and car batteries while Cd could be attributed to the washing of Ni-Cd batteries, Zn containing materials as well as petroleum fuel used in cars. Also, Cd substances from the road dust attached to car surfaces and transferred to car wash points could be another source of input [25].…”
Section: Heavy Metal Concentration In Water and Sedimentsmentioning
confidence: 99%
“…Myriophyllum spicatum [20], Elodea canadensis, Lemna minor and Leptodictyum riparium [21] with Commelina benghalensis and Cynodon dactylon [22] are among the various species whose bioaccumulation potentials for heavy metals have been investigated in sediments and other polluted environments. However, few of the studies on aquatic systems have included car wash [23] [24] [25]. In Cameroon, studies by [26] [27] and [28] focused on physico-chemical properties and phytoplankton diversity and abundance in streams under anthropogenic influences.…”
Section: Introductionmentioning
confidence: 99%